Nearly Zero Energy Buildings and Proliferation of Microorganisms A Current Issue for Highly Insulated and Airtight Building Envelopes - Di Giuseppe, Elisa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book provides a concise review of the thermo-physical phenomena which regulate heat and moisture transportation in Nearly Zero Energy Buildings envelopes, and their relationship with the growth of biological organisms. It describes the main microorganisms proliferating on contemporary building elements and within buildings. It also states the consequences of biological growth on durability, aesthetics and human health; and provides the main methods for the analytical and experimental evaluation of proliferation. Finally, through the review of recent developments, remedial actions to counter the biological phenomenon are examined, and an outline is provided for future innovations in a field not yet widely investigated.
Definitions -- Introduction -- Algal Growth on External Building Envelope -- Development of Mould in Indoor Environments -- Analytical and Experimental Methods for the Assessment of the Biological Proliferation in Buildings -- Nearly Zero Energy Buildings and Proliferation of Microorganisms -- Remedial Actions and Future Trends -- Conclusions.
Keywords: Energy efficiency; Buildings—Design and construction; Building; Construction; Engineering, Architectural; Microbial ecology; Energy Efficiency; Building Construction and Design; Microbial Ecology